Numerical prediction of aerodynamic noise from impeller blowers of straw threshing machines. (January 2020) - ZhiPing, Zhai; ZhuWei, Li; Long, Zhang; Zhongyi, Yang; Yuezheng, Lan
An impeller blower is one of the major aerodynamic noise sources in straw threshing machines. To reduce its aerodynamic noise, it is essential to understand the mechanism of gas-material-coupled unsteady flow causing aerodynamic noise. However, it is difficult to clarify the mechanism through measurement. Therefore, the following topics are studied in this article. First, a full-field transient numerical simulation of the gas and solid particulates' unsteady flow inside the impeller blower was carried out using a dense discrete phase model and a large eddy simulation turbulence model. Second, based on the Ffowcs Williams–Hawkins equation, the aerodynamic noise of the impeller blower of the straw threshing machines was numerically calculated. Finally, the numerical results were verified by aerodynamic noise test. The results indicate that (1) sound pressure level at the inlet of the impeller blower is the highest, mainly at 100 Hz, which is the fundamental frequency of the rotating impeller, while the sound pressure level at the fourth harmonic frequency of 400 Hz is the main source of the outlet. The total sound pressure level at the inlet is greater than that at the outlet. It is concluded that the dipole source of the rotating impeller is the main noise source, which was generated by the interaction of blade with the air and material as the impeller rotated. Also, acoustic attenuation, acoustic resonance, and impact noise of material and machinery play important roles in aerodynamic noise distribution. (2) The test and simulation results show good agreement, so the numerical model of aerodynamic noise is reliable. This study will provide a reference for the structural and acoustic optimization design of impeller blowers and their integration into threshing machines.